A (3, 6)-connected metal–organic framework with high CH4 binding affinity and uptake capacity1. Issue 26 (14th July 2015) - Liu, Huiyan; Wang, Qian; Zhang, Mingxing; Jiang, Jingjing
<x xml:space="preserve">Abstract</x> A (3, 6)-connected metal–organic framework with fit-3 topology, NJU-Bai16, was reported. The small pores within the framework have enabled their strong interactions with CH4. NJU-Bai16 was thereby found to exhibit high isosteric heats of CH4 adsorption and uptake capacity in low pressure region.